2020
DOI: 10.1080/1331677x.2019.1708771
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the exchange rate on the foreign trade imbalance during the economic crisis in the new EU member states and the Western Balkan countries

Abstract: This paper examines the relationship between the real exchange rate and the foreign trade imbalance in both the Western Balkan (WB) and Central and Eastern European (CEE) countries. During the most recent global economic crisis, examining the impact of the exchange rate on the balance of trade took on a particular importance. Countries used a variety of monetary policy regimes and, depending on their choice, they had different economic instruments available to deal with the crisis. The aim of the research was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
0
11
2
Order By: Relevance
“…The obtained results of the research are in line with the main conclusions of the theoretical considerations, as well as with the results of studies conducted by other researchers. Similar conclusions concerning the impact of REER on the foreign trade imbalances were reached by Rajković et al (2020). Results of their research show that during the global economic crisis, the balance of payments deficit is not impacted significantly by the exchange rate and those countries that use their own currency cannot substantially adjust their trade deficit by depreciating their currency.…”
Section: Discussionmentioning
confidence: 58%
“…The obtained results of the research are in line with the main conclusions of the theoretical considerations, as well as with the results of studies conducted by other researchers. Similar conclusions concerning the impact of REER on the foreign trade imbalances were reached by Rajković et al (2020). Results of their research show that during the global economic crisis, the balance of payments deficit is not impacted significantly by the exchange rate and those countries that use their own currency cannot substantially adjust their trade deficit by depreciating their currency.…”
Section: Discussionmentioning
confidence: 58%
“…Furthermore, the topic of interventions in exchange rates in order to support export potential due to events in global markets is also current. However, as Rajković et al (2020) showed in the example of the currencies of the Balkans and Central and Eastern Europe, currency depreciation did not have a significant effect on the trade deficit. Interestingly, Xing (2018) found the complete opposite to be true, with rising wages and the cumulative appreciation of the RMB undermining China's comparative advantage.…”
Section: Literature Reviewmentioning
confidence: 81%
“…The finding of import supports the theory of exchange rate and the changes in exchange rate. Also, Rajković, Bjelić, Jaćimović, & Verbič, (2020) predicts the association between foreign trade balance and real exchange rate undertaking Central and Eastern European (CEE) countries, and findings predict that in the economic crises scenario the nation which used their own currency experiences depreciating in the currency. Similarly there are more studies of different nation giving reflecting findings for instance, Arize, Malindretos, & Igwe, (2017); Dogru, Isik, & Sirakaya-Turk, (2019) and Choi, (2019).…”
Section: Relationship Between Exchange Rate and Trade Balancementioning
confidence: 99%